Cluster B personality symptoms in persons at genetic risk for schizophrenia are associated with social competence and activation of the right temporo-parietal junction during emotion processing - Goldschmidt, Micaela Giuliana (2014)
Personality disorders are common in nonpsychotic siblings of patients with schizophrenia, and some personality traits in this group may be associated with an increased risk for full-blown psychosis. We sought to establish if faulty right-hemisphere activation induced by social cognitive tasks, as previously described in patients with schizophrenia, is associated with specific personality symptoms in their unaffected siblings. We observed that cluster B personality symptoms in this group were inversely related to activation in the right temporo parietal junction (rTPJ, a structure critical in social cognitive processing) in response to a basic emotion processing task and also to social competence, whereas in contrast to our initial hypothesis, cluster A traits were not associated with right hemisphere activation during emotion processing or with social competence. These findings suggest the existence of clinical traits in at-risk individuals which share a common neurobiological substrate with schizophrenia, in regards to social performance.